Global Aesthetics Consensus: Botulinum Toxin Type A—Evidence-Based Review, Emerging Concepts, and Consensus Recommendations for Aesthetic Use, Including Updates on Complications. Issue 3 (March 2016) - Sundaram, Hema; Signorini, Massimo; Liew, Steven; Trindade de Almeida, Ada R.; Wu, Yan; Vieira Braz, André; Fagien, Steven; Goodman, Greg J.; Monheit, Gary; Raspaldo, Hervé
Abstract : Background: Botulinum toxin type A injection remains the leading nonsurgical cosmetic procedure worldwide, with a high rate of efficacy and patient satisfaction. Methods: A multinational, multidisciplinary group of plastic surgeons and dermatologists convened the Global Aesthetics Consensus Group to develop updated consensus recommendations with a worldwide perspective for botulinum toxin and hyaluronic acid fillers. This publication on botulinum toxin type A considers advances in facial analysis, injection techniques, and avoidance and management of complications. Results: Use of botulinum toxin has evolved from the upper face to also encompass the lower face, neck, and midface. The Global Aesthetics Consensus Group emphasizes an integrative, diagnostic approach. Injection dosage and placement are based on analysis of target muscles in the context of adjacent ones and associated soft and hard tissues. The indication for selection of botulinum toxin as a primary intervention is that excessive muscular contraction is the primary etiology of the facial disharmony to be addressed. Global Aesthetics Consensus Group recommendations demonstrate a paradigm shift toward neuromodulation rather than paralysis, including lower dosing of the upper face, more frequent combination treatment with hyaluronic acid fillers, and intracutaneous injection where indicated to limit depth and degree of action. Conclusions: The accumulation of clinical evidence and experience with botulinum toxin has led to refinements in treatment planning and implementation. The Global Aesthetics Consensus Group advocates an etiology-driven, patient-tailored approach, to enable achievement of optimal efficacy and safety in patient populations that are rapidly diversifying with respect to ethnicity, gender, and age. CLINCAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.